ANALYSIS OF THE BELA BELI KULON PROGO PROGRAM IMPLEMENTATION (Case Study : PT. Selo Adikarto Year 2013-2019) - Puspitasari, Dwi; Mahendra, Gerry Katon (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2020)
Kulon Progo is a region in Yogyakarta that ranks second lowest in people's welfare. However, in recent years, the region's economic growth has increased due to local governments, communities, and companies owned by BUMD Kulon Progo collaboration to succeed in the Bela Beli Kulon Progo Program. Pt. Selo Adikarto is a company owned by Kulon Progo Local Government. In 2010-2011 the company encountered tax debt and internal problems within the company's organization. The local government then looked for a solution for the company to avoid bankruptcy by implementing Bela Beli Kulon Progo Program. The program's primary goal is to realize the regional economy's adequacy by shaping people's behavior in preserving and buying local products. A qualitative research method was implemented in this study. At the same time, the interviews and documentation were carried out as the data collection methods. The participants of this study were chosen deliberately (non-probability sampling, purposive). They are the President Director of PT. Selo Adikarto and Head of the Road Maintenance Section Bina Marga Road Agency, Department of Public Works. The Bela Beli Kulon Progo Program at PT. Selo Adikarto has been successfully implemented. Six variables are influencing the success of this implementation. These six variables are clear policy objectives and standards; resources; quality of inter-organizational relationships; institutions/organizations manager characteristics; politic, social, and economic environments; disposition/response or executives' attitude. PT. Selo Adikarto always updates information related to company profiles and the actual developments on its economic improvement, and changes to its organizational structure by the PT. Selo Adikarto official website. PT. Selo Adikarto is still a medium-sized company; thus, it unable to maximumly support the program. Pt. Selo Adikarto had to be upscaled to a large company in order to support large-scale projects. The company management related to working capital should be taken into account and have clear and realistic business planning and reliable products.